Global determinants of coastal migration under climate change - Duijndam, Sem (2025)
Climate change-induced sea-level rise and associated flood risk will have major impacts on coastal regions worldwide, likely prompting millions of people to migrate elsewhere. Migration behavior is expected to be context-specific, but comparative empirical research on coastal migration under climate change is lacking. We address this gap by utilizing original survey data from coastal Argentina, France, Mozambique and the United States to research determinants of migration under different flood risk scenarios. Here we show that migration is more likely in higher-than in lower-income contexts, and that flood risk is an important driver of migration. Consistent determinants of migration across contexts include response efficacy, self-efficacy, place attachment and age, with variations between scenarios. Other factors such as climate change perceptions, migration costs, social networks, household income, and rurality are also important but context-specific. Furthermore, important trade-offs exist between migration and in-situ adaptation. These findings support policymakers in forging equitable migration pathways under climate change.